2016
DOI: 10.1002/anie.201608559
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Key Structural Features of an Enantioselective Peptide‐Catalyzed Acylation Utilizing Advanced NMR Techniques

Abstract: We report on a detailed NMR spectroscopic study of the catalyst-substrate interaction of a highly enantioselective oligopeptide catalyst that is used for the kinetic resolution of trans-cycloalkane-1,2-diols via monoacylation. The extraordinary selectivity has been rationalized by molecular dynamics as well as density functional theory (DFT) computations. Herein we describe the conformational analysis of the organocatalyst studied by a combination of nuclear Overhauser effect (NOE) and residual dipolar couplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 36 publications
2
46
0
Order By: Relevance
“…Second, it exhibits high degrees of selectivity despite the use of a highly‐fluxional chiral catalyst. This is contrary to the conventional view that highly selective catalysts should be fairly rigid, raising fundamental questions regarding the interplay of catalyst flexibility and selectivity . Finally, Sibi et al .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Second, it exhibits high degrees of selectivity despite the use of a highly‐fluxional chiral catalyst. This is contrary to the conventional view that highly selective catalysts should be fairly rigid, raising fundamental questions regarding the interplay of catalyst flexibility and selectivity . Finally, Sibi et al .…”
Section: Introductionmentioning
confidence: 90%
“…This is contrary to the conventional view that highly selective catalystss hould be fairly rigid, raising fundamentalq uestions regarding the interplay of catalyst flexibility and selectivity. [36,37] Finally, Sibi et al [28] observed that biaryl alcohols with electronrich substituents at the b'-position exhibit much higher selectivitiest han those with electron-poor ones. Although this was explained in terms of ap ossible non-covalent interaction betweenthese substituents and the N-acyl group, the established precedento fp···p + interactions in similara cylation reactions [32][33]35] raises the possibility that these substituent effects are due to the modulation of p···p + interactions in the stereochemistry-controllingtransition state (TS).…”
Section: Introductionmentioning
confidence: 99%
“…[8] Other studies have demonstrated their substantial influence on the stability of organometallic complexes [9] and in catalysis. [10] In recent years,n umerous computational methods were developed that give access to ac omprehensive toolbox for efficiently evaluating the dispersion interactions in molecular systems with high accuracy. [11] Nevertheless,L ondon dispersion is often regarded as negligible in solution.…”
mentioning
confidence: 99%
“…Since the first publication of the PSYCHE method in 2014, [5] a variety of experiments using the PSYCHE pulse sequence element have been introduced, including 1D 1 H NMR [5,23] , 2D 1 H-1 H TOCSY [24] and variants using band-selective excitation [25] and non-uniform sampling [26] , 2D J-resolved spectroscopy with absorption mode lineshapes (PSYCHE 2DJ [23] and RASA2DJ [27] ), z-filtered 2DJ spectroscopy with interferogram acquisition [28] , the PSYCHEDELIC [29] method for selective measurements of individual couplings, 1D 1 H NMR combined with selective TOCSY [30] , PSYCHE-EASY-ROESY [31] for direct observation of intermolecular NOEs in crowded spectra, PSYCHE-iDOSY [32] for mixture analysis, PSYCHE CPMG-HSQMBC [33] for accurate measurements of heteronuclear couplings, ultrafast multi-slice selective J-resolved spectroscopy [34] , and Inrec-PSYCHE and CPMG-PSYCHE [35] for T1 and T2 measurements. Here we discuss a few of these methods and introduce some current improvements in the application and implementation of the PSYCHE method.…”
Section: Psyche-based Experimentsmentioning
confidence: 99%